(3cJGH ehGRjf GdGMLGQ Ydi QCi HdjfGS GdMcjes - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi JhGUd fYeg hbO cfG fYOc ai cJGH ef cJH GdehGRjf HQCi HdjfGS NGUI ai Yde GdehGRjf s
(3BNQgG (B:s
(3Ke CfRdg Yf GdfGQ hUH Ydjg eGA HGQO Ke GLYdg ai bGQhQI hGSYI Gdae hTO QCSgG hGOafgG ai Pjd GdNjd GdQWH SHYI CjGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs